Answer:
![2x^3+x^2-8x-4=(2x+1)(x+2)(x-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/g4doe2zzsbd24q5japueyj958da5bbmg28.png)
Explanation:
Let's collect
between the first two terms, and -4 between the last two:
![2x^3+x^2-8x-4=x^2(2x+1) -4 (2x+1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xwjb1djrhlposdzty9anhcbgtmus3xwmeh.png)
At this point you should see there is a common factor
between both terms, then let's collect that:
![2x^3+x^2-8x-4=x^2(2x+1) -4 (2x+1) = (2x+1)(x^2-4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zlqculqy4arypv78c9nqiysk184nf0g12z.png)
Final step is recognizing a difference of squares (x and 2) in the second bracket, to end up our work!
![2x^3+x^2-8x-4=x^2(2x+1) -4 (2x+1) = (2x+1)(x^2-4) =(2x+1)(x+2)(x-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/e4msxqtag540ghlik646g2cfjz2be8bko5.png)